A multidisciplinary consensus document on follow‐up strategies for patients treated with percutaneous coronary intervention. (27th November 2014) - Rossini, Roberta; Oltrona Visconti, Luigi; Musumeci, Giuseppe; Filippi, Alessandro; Pedretti, Roberto; Lettieri, Corrado; Buffoli, Francesca; Campana, Marco; Capodanno, Davide; Castiglioni, Battistina; Cattaneo, Maria Grazia; Colombo, Paola; et al.
Abstract : The number of percutaneous coronary interventions (PCI) is increasing worldwide. Follow‐up strategies after PCI are extremely heterogeneous and can greatly affect the cost of medical care. Of note, clinical evaluations and non‐invasive exams are often performed to low risk patients. In the present consensus document, practical advises are provided with respect to a tailored follow‐up strategy on the basis of patients' risk profile. Three strategies follow‐up have been defined and types and timing of clinical and instrumental evaluations are reported. Clinical and interventional cardiologists, cardiac rehabilitators, and general practitioners, who are in charge to manage post‐PCI patients, equally contributed to the creation of the present document. © 2014 Wiley Periodicals, Inc.